2019
DOI: 10.1128/iai.00527-19
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Tropism in Streptococcal Infection: Wild-Type M1T1 Group AStreptococcusIs Efficiently Cleared by Neutrophils Using an NADPH Oxidase-Dependent Mechanism in the Lung but Not in the Skin

Abstract: Group AStreptococcus(GAS) commonly causes pharyngitis and skin infections. Little is known why streptococcal pharyngitis usually does not lead to pneumonia and why the skin is a favorite niche for GAS. To partially address these questions, the effectiveness of neutrophils in clearing wild-type (wt) M1T1 GAS strain MGAS2221 from the lung and from the skin was examined in murine models of intratracheal pneumonia and subcutaneous infection. Ninety-nine point seven percent of the MGAS2221 inoculum was cleared from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Here, when mice were depleted of neutrophils, the bacterial burden of the SLSdeficient S. pyogenes nasopharyngeal infection was unaffected (Fig 4). We also noted that neutrophil-deplete mice infected with the wildtype bacteria was also unaffected yet had increased amounts of bacteria present in their lungs (S3 Fig) , which concurs with a study highlighting the role of neutrophils in preventing streptococcal pneumonia in mice [47]. Although neutrophil depletion did not restore bacterial burden in the nasopharynx, bacterial burden was recovered in a streptococcal skin infection (Fig 4E), which was expected given that the lack of SLS is associated with increased neutrophils during skin infection in mice [24].…”
Section: Plos Pathogenssupporting
confidence: 90%
“…Here, when mice were depleted of neutrophils, the bacterial burden of the SLSdeficient S. pyogenes nasopharyngeal infection was unaffected (Fig 4). We also noted that neutrophil-deplete mice infected with the wildtype bacteria was also unaffected yet had increased amounts of bacteria present in their lungs (S3 Fig) , which concurs with a study highlighting the role of neutrophils in preventing streptococcal pneumonia in mice [47]. Although neutrophil depletion did not restore bacterial burden in the nasopharynx, bacterial burden was recovered in a streptococcal skin infection (Fig 4E), which was expected given that the lack of SLS is associated with increased neutrophils during skin infection in mice [24].…”
Section: Plos Pathogenssupporting
confidence: 90%
“…For example, a recent report by Lei et al details the differences in neutrophil response to Group A Streptococcus in the lungs compared to the skin. While this bacterial species is efficiently cleared from the lungs of mice by a nicotinamide adenine dinucleotide phosphate oxidase (NOX)-dependent mechanism, clearance is impaired in the skin [55]. This discrepancy may be due to creation of an anoxic environment in the skin, which favors the growth of this organism but hampers oxidative burst by neutrophils.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Additional roles of SLS during host infections are also becoming clear, since the toxin is highly upregulated during invasive GAS infections, and it has been shown that GAS lacking the toxin exhibit significant deficiencies in causing skin lesions and disseminating in vivo ( Datta et al., 2005 ; Hirose et al., 2019 ). SLS has also been shown to contribute to the degradation of epithelial cell junctions to promote invasive disease, induce lysis of multiple nonerythrocytic cell types, and have other significant effects in both in vivo and in vitro infection models ( Ginsburg, 1972 ; Betschel et al., 1998 ; Miyoshi-akiyama et al., 2005 ; Sumitomo et al., 2011 ; Flaherty et al., 2015 ; Hirose et al., 2019 ; Lei et al., 2019 ). These include the ability of SLS to exacerbate the host inflammatory response, thereby disrupting the ability of the host immune system to clear the infection without over-activation that results in damaging hyperinflammation ( Flaherty et al., 2015 ; Castiglia et al., 2016 ; Flaherty et al., 2018 ; von Beek et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%